(untitled) (مجلة جامعة اللاذقية - سلسلة العلوم الأساسية, 2018)
يهدف البحث إلى دراسة الخواص الفيزيائية والميكانيكية للفلزات المكونة للصخور كتحديد نوع الصخر، المحتوى الفلزي، الكثافة، وزاوية الاحتكاك، والتماسك، وتأثير هذه الصفات على مقدرة تماسك هذه الصخور وقدرتها على تحمل الأثقال، أو تعرضها للانزلاق، وكيفية معالجة هذه الانزلاقات، والحد من خطورتها . The paper aims at studying the physical and mechanical properties which form rocks, such as determining rock type, mineral content, density, internal range of friction, density, and the influence of these properties on minerals which form rocks in the study area. The purpose is to determine the ability of these rocks to hold together, tolerate weights, their liability to slide, and how to deal with sliding and reduce their dangerous effects.